MRI- And CT-determined changes of dysphagia / aspiration-related structures (DARS) during and after radiotherapy - Pigorsch, Steffi U.; May, Chaline; Kessel, Kerstin A.; Graf, Simone; Bier, Henning; Nuesslin, Fridtjof; Waschulzik, Birgit; Combs, Stephanie E. (PLoS ONE, 2020)
Purpose The concept of dysphagia/aspiration-related structures (DARS) was developed against the background of severe late side effects of radiotherapy (RT) for head and neck cancer (HNC). DARS can be delineated on CT scans, but with a better morphological discrimination on magnetic resonance imaging (MRI). Swallowing function was analyzed by use of patient charts and prospective investigations and questionnaires. Method Seventeen HNC patients treated with intensity-modulated radiotherapy (IMRT) ± chemotherapy between 5/2012 – 8/2015 were included. Planning CT (computed tomography) scans and MRIs (magnetic resonance imaging) prior, during 40 Gray (Gy) radiotherapy and posttreatment were available and co-registered to delineate DARS. The RT dose of each DARS was calculated. Five patients were investigated posttreatment for swallowing function and assessed by means of various questionnaires for quality of life (QoL), swallowing, and voice function. Results By retrospective comparison of DARS volume, a significant change in four of eight DARS was detected over time. Three increased and one diminished. The risk of posttreatment dysphagia rose by every 1Gy above the mean dose (D mean) of RT to DARS. 7.5 was the risk factor for dysphagia in the first 6 months, reducing to 4.7 for months 6-12 posttreatment. For all five patients of the prospective part of swallowing investigations, a function disturbance was detected. These results were in contrast to the self-assessment of patients by questionnaires. There was neither a dose dependency of D mean DARS volume changes over time nor of dysphonia and no correlation between volume changes, dysphagia or dysphonia. Conclusion Delineation of DARS on MRI co-registered to planning CT gave the opportunity to differentiate morphology better than by CT alone. Due to the small number of patients with complete MRI scans over time, we failed to detect a dose dependency of DARS and swallowing and voice disorder posttreatment.
CRIS-Team Scopus Importer:2023-03-08